VEGF-A is associated with early degenerative changes in cartilage and subchondral bone. (2nd November 2018) - Zupan, Janja; Vrtačnik, Peter; Cör, Andrej; Haring, Gregor; Weryha, Georges; Visvikis-Siest, Sophie; Marc, Janja
Abstract: Paired cartilage and subchondral bone of subjects with no clinical history of joint disorders were analyzed to determine whether antioxidant enzymes, inflammatory cytokines and growth factors can be linked to a pre-osteoarthritis. Tissue explants were phenotyped according to Osteoarthritis Research Society International grading and micro-computed tomography, and also screened for the expression of several markers using quantitative polymerase chain reaction. The expression of these same genes was measured in SW1353 cells treated with hydrogen peroxide, to gain insight into the pathways involved with oxidative stress responses. Vascular endothelial growth factor A (VEGF-A) was up-regulated in the cartilage samples that showed early cartilage or bone degeneration. Oxidative stress in chondrocytes provoked up-regulation of interleukin-1β, interleukin-6, aggrecan, and SRY-box containing gene 9. Our results confirm the hitherto evidence of the deteriorating effects of the oxidative stress on cartilage and suggest the link between VEGF-A and pre-osteoarthritis.